Music of Thrace. An Interdisciplinary Approach Evros - Dawe, Kevin N. (Oxford University Press, Oxford, 2003)
RESUMEN: Editado por Loukia Droulia, Lambros Liavas. The Friends of Music Society, Athens, 1999.